Further Structural Modification of Sulfur-Stabilized Silicon Cations with Binaphthyl Backbones - Shaykhutdinova, Polina; Oestreich, Martin (Synthesis, 2019)
The synthesis and spectroscopic characterization of two novel cationic silicon–sulfur Lewis pairs with a chiral 4,4′-disubstituted binaphthyl silepine backbone are described. Both Lewis acids induce significant enantioselectivity in the model Diels–Alder reaction of cyclohexa-1,3-diene and chalcone but additional substitution of the binaphthyl backbone exerts a minimal effect on enantioinduction compared to previously reported Lewis acids. Another silicon cation with a chiral spirocyclic backbone induces enantioselectivity in the same range but its synthesis is laborious.
Keywords: asymmetric catalysis; chirality; Diels–Alder reaction; Lewis acids; silylium ions